SENAM NIFAS DAN MOBILISASI DINI TERHADAP PENURUNAN FUNDUS UTERI PADA IBU POST PARTUM DI PUSKESMAS TEMINDUNG - rahmawati wahyuni; Nursari Abdul Syukur (Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur, 2020)
Background: Postpartum bleeding can be caused by uterine atony, laceration, retensio placenta, utero inversion and blood clotting. In general, by puerperal gymnastics, it can accelerate the process of restoring the condition of mothers after childbirth and prevent possible complications during the time of the puerperium. The purpose of this study was to determine the effect of puerperal gymnastics on the decrease in fundal height of postpartum mothers in the Puskesmas Temindung . Research method: This research is a pre experimental research with pre test-post test control group design. The subject of the study was all post partum mothers who gave birth at the Puskesmas Temindung in Agust-October 2019. The samples consisted of 2 groups with 48 respondents, which were selected using the consecutive sampling technique. Analysis of independent T-test statistics with significance level 0.05. Result: The results showed a significant difference from the decline of TFU in the post-partum mother between the group doing puerperal gymnastics and not puerperal gymnastics in the Puskesmas Temindung proved with P-value = 0.002. Conclusion and suggestion: In this study, Ho refused to show that there was an influence of puerperal gymnastics on the decrease in fundal height of postpartum mothers in the Puskesmas Temindung . It is hoped that puerperal gymnastics is applied by Puskesmas Temindung because it is useful in the process of restoring the condition of postpartum mothers.